Application of copper thiocyanate for high open‐circuit voltages of CdTe solar cells. (22nd July 2015) - Paudel, Naba R.; Yan, Yanfa
Abstract: Copper thiocyanate (CuSCN) has proven to be a low‐cost, efficient hole‐transporting material for the emerging organic–inorganic perovskite solar cells. Herein, we report that CuSCN can also be applied to CdTe thin‐film solar cells to achieve high open‐circuit voltages ( VOC s). By optimizing the thickness of the thermally evaporated CuSCN films, CdTe cells fabricated by close space sublimation in the superstrate configuration have achieved VOC s as high as 872 mV, which is about 20–25 mV higher than the highest VOC for the reference cells using the standard Cu/Au back contacts. CuSCN is a wide bandgap p ‐type conductor with a conduction band higher than that of CdTe, leading to a conduction band offset that reflects electrons in CdTe, partially explaining the improved VOC s. However, due to the low conductivity of CuSCN, CdTe cells using CuSCN/Au back contacts exhibited slightly lower fill factors than the cells using Cu/Au back contacts. With optimized CdS:O window layers, the power conversion efficiency of the best CdTe cell, using CuSCN/Au back contact, is 14.7%: slightly lower than that of the best cell (15.2%) using Cu/Au back contact. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, we report that CuSCN could be a good electron reflector for CdTe solar cells. We have found CdTe cells with CuSCN/Au back contacts can lead to VOC improvements by 20–25mV as compared with the cells using standard Cu/Au back contacts. With CuSCN buffer layer, our CdTe solar cells have demonstrated VOC s as high as 872 mV. We believe that the results reported herein suggest a new way to improve the performance of CdTe solar cells.